Soluble E-selectin in multiple sclerosis: raised concentrations in patients with primary progressive disease. Issue 1 (January 1996) - Giovannoni, G; Thorpe, J W; Kidd, D; Kendall, B E; Moseley, I F; Thompson, A J; Keir, G; Miller, D H; Feldmann, M; Thompson, E J
Abstract : OBJECTIVE--To determine whether concentrations of soluble E-selectin (sE-selectin), an immunological marker of endothelial activation, were correlated with gadolinium-DPTA enhancement on MRI in patients with multiple sclerosis. METHODS--Serial sE-selectin concentrations were measured in 28 patients with multiple sclerosis undergoing monthly gadolinium (Gd) enhanced MRI of the brain and spinal cord, and in 10 control subjects. C reactive protein (CRP), von Willebrand factor (vWF), and tumour necrosis factor-alpha (TNF alpha) were also determined. RESULTS--Primary progressive patients had significantly increased sE-selectin concentrations compared with the relapsing remitting and secondary progressive patients who had normal sE-selectin concentrations (22.2 (SD1 6.1) ng/ml v 9.8 (SD2.1) ng/ml and 7.7 (SD2.7) ng/ml, respectively, P = 0.03). This difference was attributable to five of the 10 primary progressive patients who had persistently raised sE-selectin concentrations, with relatively inactive MRI studies. No correlation could be found between sE-selectin concentrations and Gd enhancement on MRI, but a close correlation existed between mean concentrations of sE-selectin and TNF alpha (r = 0.71, P < 0.001). Despite raised sE-selectin and TNF alpha concentrations, primary progressive patients had normal CRP concentrations (1.03 (SD1.14) mg/l), which were significantly lower than the relapsing remitting (3.16 (SD2.54) mg/l) and secondary progressive patients (2.28 (SD2.1) mg/l, P = 0.03). Raised CRP concentrations did correlate with infectious episodes, clinical relapse, and Gd enhancement, and were significantly raised when no MRI activity was found. Concentrations of vWF were normal in all patient groups. CONCLUSIONS--The results further high-light the differences between patients with primary progressive and those with relapsing remitting/secondary progressive multiple sclerosis.